New Media to Develop Graduate Attributes of Science Students. - Rifkin, Will; Longnecker, Nancy; Leach, Joan; Davis, Lloyd (Australian Learning and Teaching Council (ALTC), 2012)
Final report from a project that enabled science students to gain new media communication skills, preparing them to be professionals who can engage the public on issues involving science. The students learned from science lecturers coached by science communication academics. This partnership enabled addressing science communication within core science subjects. Members of this cross-disciplinary community of practice engaged students in multimedia web publication as a form of authentic learning, a favoured avenue for graduate attribute development. Participatory design of teaching materials included 'early adopter' science lecturers recruited at conferences and university workshops. Recruits were trained to be agents of change, coaching colleagues on these new teaching methods and materials. Evaluation assessed learning impact, ease of use of teaching/learning materials, and quality of the multimedia web publications. Dissemination occurred through workshops and online.